Hubungan Pengetahuan Diet Rendah Garam dengan Tekanan Darah Lansia Penderita Hipertensi di Puskesmas Kelurahan Ragunan - Halidah Zainal Arivin; Naziyah Naziyah; Cholisah Suralaga (Universitas Malahayati Lampung, 2023)
ABSTRACT Blood pressure is the energy needed by blood to supply blood vessels and circulate blood throughout the body. Hypertension is not an ordinary disease, hypertension is known as the